2021
DOI: 10.3390/jcdd8070074
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sutureless and Rapid Deployment Prostheses in Challenging Reoperations

Abstract: Sutureless and rapid-deployment bioprostheses have been introduced as alternatives to traditional prosthetic valves to reduce cardiopulmonary and aortic cross-clamp times during aortic valve replacement. These devices have also been employed in extremely demanding surgical settings, as underlined in the present review. Searches on the PubMed and Medline databases aimed to identify, from the English-language literature, the reported cases where both sutureless and rapid-deployment prostheses were employed in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…6 Furthermore, given the multiple aforementioned challenges posed by this case-such as the reoperative nature or hostile homograft root-this was considered a high-risk operation. 9…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Furthermore, given the multiple aforementioned challenges posed by this case-such as the reoperative nature or hostile homograft root-this was considered a high-risk operation. 9…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, given the multiple aforementioned challenges posed by this case—such as the reoperative nature or hostile homograft root—this was considered a high‐risk operation 9 . However, implantation of the sutureless Perceval valve helped minimize cardiopulmonary bypass time and thereby somewhat mitigate the risk profile of the case.…”
Section: Discussionmentioning
confidence: 99%
“…This has been demonstrated when unsatisfactory repair with the persistence of AI occurs intraoperatively, 4 and also when AI recurrence is observed late after initial repair. 5 In all such cases, successful reoperation has been reported showing the stability of the annulus after the remodeling even in the presence of aortic insufficiency and early failure.…”
Section: Transcatheter Aortic Valve Replacement After Valve-sparing A...mentioning
confidence: 98%
“…We agree with Dhanekula and colleagues 2 on the importance of the PSB in providing larger effective orifice areas compared with standard stented bioprostheses so as to minimize the occurrence of patient–prosthesis mismatch. However, in the specific setting we reviewed, 4 we also believe that in elderly, less active patients the problem of patient–prosthesis mismatch might not be so crucial compared with providing a rapid, lower-risk reoperation and a successful outcome.…”
mentioning
confidence: 99%
“…This issue has been recognized by Dhanekula and colleagues 2 but was more specifically addressed in our recent review of the literature, which has unfortunately been overlooked. 4 We have showed that sutureless and rapid-deployment bioprostheses were used in a variety of challenging situations, significantly simplifying such procedures. We identified a total of 25 patients in whom such prostheses were used in complex redo procedures: 17 of them had a stentless bioprosthesis (as AVR and root replacement in 11), 6 patients a homograft (4 AVR and 2 aortic root replacements), and 2 a valve-sparing procedure.…”
mentioning
confidence: 99%